Values of 15 STR in Beninese population’s filiation testS - AZONBAKIN, AZANDÉGBÉ SIMON; BIGOT, CÉDRIC EGNONWA PARFAIT; ADJAGBA, Marius; DEBAILLY, Max; DARBOUX, Max; Laleye, Anatole (My University, 2019)
The population genetic characterization is very important in medicine and particularly in medical anthropology. This characterization can be done using SNP (Single Nucleotide Polymorphism), haplotypes of the genes of the HLA system, and with STR (Short Tandem Repetition). STRs, which are small nucleotides repetition used to characterize populations, are very interesting in parentage tests. In this study, the DNA was extracted from the peripheral blood taken from 251 Beninese born from Beninese parents without any parental link. Fifteen (15) STR, including D3S1358, VWA, FGA, D8S1179, D21S11, D18S51, D5S818, D13S317, D7S820, TH01, TPOX, CSF1PO, D19S433, D2S1338, D16S539 were investigated. The amplified PCR products were separated by capillary electrophoresis on an ABI 310 XL genetic analyzer (Applied Biosystems). The diversity software version 1.9.89 was used for the calculation of allele frequencies, number of alleles per locus, heterozygosity and the Hardy-Weinberg balance test in the population. Forensic parameters such as Discrimination Power (PD), Exclusion Power (PE), Informative Content of Polymorphism (ICP) are calculated using the software R. Six loci (D21S11, D7S820, D18S51, THO1, D5S818 and FGA) out of the fifteen studied diverged from steady-state even after the bonferroni correction. The STRs used for paternity research and for forensic identification in Benin are very discriminating with a combined exclusion power in order of 0.9999 and a combined discrimination power higher than 0.9999999999. Therefore they are very informative in the filiation and identification tests of persons.
Keywords: STR; Genetic diversity; Filiation test; Forensic identification; Legal medicine; Benin.